2016
DOI: 10.1002/2015jd023805
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate ion spikes in ice cores not suitable as proxies for solar proton events

Abstract: Nitrate ion spikes in polar ice cores are contentiously used to estimate the intensity, frequency, and probability of historical solar proton events, quantities that are needed to prepare for potentially society‐crippling space weather events. We use the Whole Atmosphere Community Climate Model to calculate how large an event would have to be to produce enough odd nitrogen throughout the atmosphere to be discernible as nitrate peaks at the Earth's surface. These hypothetically large events are compared with pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(89 citation statements)
references
References 109 publications
(330 reference statements)
9
80
0
Order By: Relevance
“…In contrast to previous hypothetical estimates3, our analysis is based on the latest event strength assessment69, which, as we show, is also supported by good agreement between modelled and observed 10 Be deposition variability. Similarly to prior conclusions1617, our results suggest that even an extreme SEP event cannot be resolved in ice core nitrate time-series devaluating it as a potential proxy for SEP events. Since the analyzed SEP event is the strongest known in the Holocene412, our results can serve as a realistic upper bound (worst-case scenario) of the possible effect of SEP events on the atmosphere.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In contrast to previous hypothetical estimates3, our analysis is based on the latest event strength assessment69, which, as we show, is also supported by good agreement between modelled and observed 10 Be deposition variability. Similarly to prior conclusions1617, our results suggest that even an extreme SEP event cannot be resolved in ice core nitrate time-series devaluating it as a potential proxy for SEP events. Since the analyzed SEP event is the strongest known in the Holocene412, our results can serve as a realistic upper bound (worst-case scenario) of the possible effect of SEP events on the atmosphere.…”
Section: Discussionsupporting
confidence: 81%
“…Since NO x is a precursor for atmospheric nitrate, it was suggested that strong SEP events can be detected as sharp spikes in records of nitrate in polar ice15. However, this was debated both experimentally for the Carrington event16 and theoretically17. If a nitrate record was indeed a proxy for strong SEP events of the past1118, the extreme event of 774 AD would be clearly identified in polar nitrate series.…”
Section: Resultsmentioning
confidence: 99%
“…This work was criticized by Smart et al (2014), who stated that the resolution of the analyzed series was not high enough and could have led to missing the spike, which was counter-argued by Wolff et al (2016) that even a fine time resolution does not reveal the peaks. It was also discussed theoretically (Duderstadt et al 2016) that a realistic SEP event can hardly produce sufficient amount of nitrate to leave a strong pulse-like signature in an ice core. Usoskin and Kovaltsov (2012) calculated, from the F 30 fluence proposed by McCracken et al (2001) for the Carrington event, the 10 Be production and showed that, if the Carrington SEP event was so strong, it would have necessarily produce a spike in the annually resolved 10 Be record, which however contradicts to the real data from NGRIP and Dye3 ice cores.…”
Section: Nitrates In Polar Icementioning
confidence: 99%
“…Duderstadt et al . [] conduct comprehensive chemical transport modeling that includes background HNO 3 . This comment addresses these differences and also corrects misrepresentations regarding Duderstadt et al .…”
Section: Introductionmentioning
confidence: 77%
“…[] and Duderstadt et al . [] are listed as companion papers, although the contents of Melott et al . [] remained confidential prior to publication.…”
Section: Introductionmentioning
confidence: 99%